Keamanan Data Dan Informasi Dier Sosialisasi Keamanan Data dan Informasi Era Digital di MA Cimalaka Kabupaten Sumedang - Zulkifli, Ridwan (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2025)
The digital era has brought fundamental changes in the management, storage, and transmission of data and information across various sectors, including government, industry, education, and daily life. The rapid development of information technology, such as cloud computing, the Internet of Things (IoT), and big data has enhanced efficiency and ease in data processing. However, on the other hand, this progress also opens gaps to various security threats that are becoming increasingly complex and sophisticated. Cyber attacks such as hacking, data theft, DDoS (Distributed Denial of Service) attacks, phishing, malware, and ransomware have become a serious challenge in maintaining the confidentiality, integrity, and availability of data and information. This research aims to provide comprehensive knowledge about various aspects of data and information security in the digital era, including protection techniques used to secure data from both internal and external threats. This activity uses the Participatory Action Research (PAR) method, which was conducted in MA Cimalaka, Sumedang Regency. The results indicate that participants have understood the importance of data security in facing various challenges in the digital era.